1983
DOI: 10.1002/1097-0142(19831001)52:7<1301::aid-cncr2820520728>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hodgkin's disease. A report of 12 cases and review of the literature

Abstract: Intracranial involvement by Hodgkin's disease is rare. Of the 30 previously reported cases, in many of which central nervous system (CNS) disease was documented postmortem, no associated risk factors have been elucidated, and response to treatment has been poor. This report cites 12 additional cases treated at the Stanford University Medical Center, five of whom have enjoyed prolonged freedom from intracranial relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 18 publications
4
69
0
Order By: Relevance
“…Because of the presence of fibrosis, RDD-CNS may have a distinctly nodular appearance suggestive of the nodular sclerosing variant of Hodgkin's disease. Hodgkin's disease occurring in the CNS is extremely rare and is typically associated with relapse (30). Although classic Reed Sternberg cells are readily distinguished from RDD histiocytes, mononuclear variants, particularly lacunar cells may mimic SHML histiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the presence of fibrosis, RDD-CNS may have a distinctly nodular appearance suggestive of the nodular sclerosing variant of Hodgkin's disease. Hodgkin's disease occurring in the CNS is extremely rare and is typically associated with relapse (30). Although classic Reed Sternberg cells are readily distinguished from RDD histiocytes, mononuclear variants, particularly lacunar cells may mimic SHML histiocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence has been reported as 0.2% to 0.5% of all HL cases, but a recent review of 14 868 patients identified only 2 cases of HL involving the CNS. [1][2][3] Most reports consist of single cases or small case series highlighting our limited knowledge about the clinical characteristics, prognosis, and management of this neurologic complication of HL. [4][5][6][7][8] Consequently, there is no consensus to guide therapeutic decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…CNS Hodgkin's disease has been described in patients with disseminated disease, particularly those with relapse involving extranodal sites (Cuttner et al, 1979;Dujovny et al, 1980;Sapozink and Kaplan, 1983). Primary Hodgkin's disease isolated to the CNS is exceedingly rare (Algers et al, 1981;Wood and Coltman, 1973).…”
Section: Discussionmentioning
confidence: 99%